1996
DOI: 10.1111/j.1469-8137.1996.tb01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary vegetational history at Navarrés, Eastern Spain. A two core approach

Abstract: S U M MARYPercentage and concentration pollen diagrams are presented for two cores (taken 5 m apart) at an upper Pleistocene and Hoiocene site at Navarres (Valencia, eastern Spain). Chronological information is provided by an internally consistent radiocarbon dating series that extends from c. 20700 to 3075 yr BP. The results highlight the dangers of relying on a single core in interpreting the patterns of variation of particular taxa. Significant palynological differences, seemingly locational, are described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…Conditions more wooded than today may have been widespread in central and southern Spain during the mid-Holocene. Carrión and Dupré (1996) describe the replacement of Pinus-dominated forest by Quercus scrub in eastern Spain after 5000 yr BP. Garcia Antón et al (1986) recorded high levels (Ͼ50%) of arboreal pollen, mainly Pinus and Quercus, in basal deposits from a site less than 120 km to the west of the Sierra de Alcaraz, and their results are also in accordance with the palaeoecological data from Alcaraz and El Jardin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conditions more wooded than today may have been widespread in central and southern Spain during the mid-Holocene. Carrión and Dupré (1996) describe the replacement of Pinus-dominated forest by Quercus scrub in eastern Spain after 5000 yr BP. Garcia Antón et al (1986) recorded high levels (Ͼ50%) of arboreal pollen, mainly Pinus and Quercus, in basal deposits from a site less than 120 km to the west of the Sierra de Alcaraz, and their results are also in accordance with the palaeoecological data from Alcaraz and El Jardin.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, the more continental and arid central and southern Spain has yielded little evidence. Exceptions are the records described by Pons and Reille (1988) from Padul at the eastern foot of the Sierra Nevada, close to Granada, and by Carrión and Dupré (1996) from Navarrés in Valencia province. Both the Padul and Navarrés sequences extend back into the last glacial.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The colonisation by Fagus is generally time-transgressive, starting during the Lateglacial in Sierra de Neila, but delaying its arrival to c. 5700 cal. yr BP or even later in most of northern Spain (Peñalba et al, 1997;Ruíz-Zapata et al, 2002, 2003a, the Pyrenees (Montserrat, 1992), Cataluña in Banyoles (Pérez-Obiol and Julià, 1994), Sierra de Cabrera in La Roya, Sanabria Marsh (Allen et al, 1996), Sanguijelas and Lleguna (Muñoz-Sobrino et al, 2004), Central Spain in Burgomillodo (Díez et al, 2002), and CC-17 core in Tablas de Daimiel, La Mancha Plain Valdeolmillos, 2004); Navarrés (Carrión and Dupré, 1996;Carrión and van Geel, 1999), Villena , and Tossal de la Roca (Cacho et al, 1995) in eastern Spain, and characteristically Padul in the south (Pons and Reille, 1988). These, among other sites, represent a geographically wide spectrum of sensitive sites to the Younger Dryas cold-dry period.…”
Section: Expected Sequences: Climate-sensitive Vegetation Changesmentioning
confidence: 99%
“…Palynological, anthropological, and archeological evidences demonstrated the presence of some forms of olive during the last glaciation in the western and eastern Mediterranean regions 18 000 years BC (Carrion and Dupre, 1996;Watts et al, 1996). Numerous studies confirmed that olives have been present for several thousands of years before its domestication in the Mediterranean basin, particularly in the Middle East.…”
Section: History Origin and Distributionmentioning
confidence: 82%